(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study focused on the antibiogram profiling of Staphylococcus aureus and coagulase-negative Staphylococcus spp. (CoNS) and the detection of icaA and blaZ genes from bovine raw milk samples. Materials and Methods: Bovine milk samples were collected from dairy farms, and Staphylococcus spp. were isolated and identified via conventional and molecular screening. Disk diffusion test (DDT) was implemented to determine the resistance pattern. Biofilm and β-lactamase-producing Staphylococcus spp. were identified via amplification of the icaA and blaZ genes. Methicillin-resistant Staphylococcus aureus and CoNS were identified by DDT and PCR of the mecA gene. Results: From 63 samples, 35 were confirmed as Staphylococcus spp., of which 16 (25.39%) S. aureus isolates were coagulase-positive, while 19 (30.16%) were negative. PCR confirmed that 50% (8/16) of S. aureus and 36.84% (7/19) of CoNS possessed the icaA gene. All S. aureus isolates were found resistant to penicillin-G (P) both phenotypically and genotypically. The isolates were also resistant to erythromycin (ERY) and oxytetracycline (TET). While CoNS showed high to reduced resistance against P, TET, ERY, and azithromycin, no S. aureus isolates were resistant to sulfamethoxazole, while 10.53% of CoNS isolates were. All S. aureus and CoNS isolates were susceptible to vancomycin and gentamicin. MR was exhibited by 37.5% of S. aureus and 42.10% of CoNS isolates. Moreover, S. aureus and CoNS had 56.25% and 52.63% multidrug-resistant (MDR) isolates, respectively. Conclusion: The present study revealed the presence of a biofilm-producing, MDR staphylococcal strain in milk that might endanger consumers. Routine surveillance and monitoring, along with antimicrobial resistance learning, can reduce risks. Adv. Vet. Anim. Res., 11(2): 455-462, June 2024 http://doi.org/10.5455/javar.2024.k795